Restrictive US trade policy has a significantly negative effect on financial markets - Lukas Boer; Lukas Menkhoff; Malte Rieth (DIW Weekly Report, 2021)
With its America First strategy, the former US administration turned away from an internationally oriented trade policy. It attempted to assert its interests, especially vis-à-vis China, with bilateral and mostly restrictive measures such as import tariffs. This Weekly Report shows that the costs of such a strategy are immense, at least in the medium-term analysis conducted: Almost all US industries were negatively affected by the US trade policy. This effect can be seen in the forward-looking financial markets, which anticipate the possible effects of tariff changes. Stock prices declined significantly and the US dollar exchange rate rose as a result of the increasing uncertainty. Beyond this, the measures against China also negatively affect the leading stock indices of many other countries. China's retaliatory measures put additional pressure on US companies. As few firms profit in this situation, the rationale for a restrictive trade policy cannot be based in economic gains. While the current administration is still maintaining a restric-tive trade policy as of July 2021, this study shows that a broad return to a multilaterally oriented trade policy is in the interest of most market participants.
Keywords: F13; F51; G10; 330; Trade policy shock; structural VAR; stock prices; exchange rates; interest rates; heteroskedasticity